The Influence of Brand Image and Green Product on Green Purchase Decision: A Case Study of Somethinc Skincare - Esa Afrilia Saputri; Maulana Agung Pratama; Prasetya Nugeraha (Cita konsultindo, 2026)
This study aims to evaluate the impact of brand image and green products on environmentally friendly purchasing decisions for Somethinc skincare products in Indonesia. The international cosmetics industry, including the domestic industry, has experienced significant expansion but faces obstacles related to sustainability and the phenomenon of greenwashing. The method used is an integrative quantitative approach with a sample of 97 respondents in Bandar Lampung who have used Somethinc products. Data collection was conducted through a questionnaire with a Likert scale and analyzed using multiple linear regression. The results of the study show that both partially and simultaneously, brand image and green products have a positive and significant influence on green purchasing decisions. Brand image plays a role in shaping initial trust, while green product attributes provide concrete verification of the brand's commitment to sustainability. Practically, this study provides managerial implications for Somethinc's marketing strategy in increasing the loyalty of environmentally conscious consumers in a growing market.